Positron emission tomography imaging of the P2X7 receptor with a novel tracer, [18F]GSK1482160, in a transgenic mouse model of Alzheimer's disease and healthy non‐human primates - Yifan Qiu; Lei Bi; Guolong Huang; Zhijun Li; Huiyi Wei; Guocong Li; Junjie Wei; Kai Liao; Min Yang; Peizhen Ye; Yongshan Liu; Xianxian Zhao; et al. (Brain-X, 2024)
Abstract This study aimed to evaluate [18F]GSK1482160 Positron emission tomography imaging for targeting P2X7R, a biomarker for neuroinflammation. Studies of acute neuroinflammation in rodents and transgenic mice with Alzheimer's disease (AD), as well as wild‐type (WT) controls, were conducted via PET‐CT‐MRI scans after tail vein injection of [18F]GSK1482160. Imaging was quantified based on the time‐activity curve, the standardized uptake value ratio, and the binding kinetics distribution volume ratio (DVR) to assess the expression of P2X7R. Tissues were collected post‐PET for immunofluorescence staining. Correlation analysis was performed between DVR and Morris water maze test results. Finally, dynamic Positron Emission Tomography‐Magnetic Resonance Imaging (PET‐MRI) scans were performed in healthy non‐human primates (NHPs). Our study demonstrated that AD mice had a significantly higher DVR than WT mice in the hippocampus (0.92 ± 0.06 vs. 0.79 ± 0.02, p < 0.05), cortex (1.09 ± 0.03 vs. 0.88 ± 0.04, p < 0.05), and striatum (1.02 ± 0.10 vs. 0.83 ± 0.1, p < 0.05). Immunofluorescence staining showed increased expression of P2X7R in the AD, along with its colocalization with activated microglia and astrocytes. Correlation analysis indicated that brain regions with higher binding of [18F]GSK1482160 (i.e., the cortex, striatum, and hippocampus) were more vulnerable to cognitive impairment. PET‐MRI scans of healthy NHPs demonstrated the feasibility of brain penetration and P2X7R target engagement for the translation of [18F]GSK1482160 in human studies.